Successful management of pulmonary edema secondary to accidental electrocution in a young dog - Eduardo A. Díaz; Carolina Sáenz; Diana Torres; Andrés Silva; Gilberto Segnini (BMC Veterinary Research, 2024)
Abstract Background Human records describe pulmonary edema as a life-threatening complication of electric shock. Successful management requires prompt recognition and intensive care. However, in companion animals, electrocutions are rarely reported, even though domestic environments are full of electrical devices and there is always the possibility of accidental injury. Therefore, it is important for veterinarians to know more about this condition in order to achieve successful patient outcomes. Case presentation A 3-month-old male Labrador Retriever was presented with a history of transient loss of consciousness after chewing on a household electrical cord. On admission, the puppy showed an orthopneic position with moderate respiratory distress. Supplemental oxygen via nasal catheter was provided, but the patient showed marked worsening of respiratory status. Point-of-care ultrasound exams suggested neurogenic pulmonary edema due to electrical shock close to the central nervous system and increased B-lines without evidence of cardiac abnormalities. Mechanical ventilation of the patient was initiated using volume-controlled mode with a tidal volume of 9 to 15 ml/kg until reaching an end-tidal carbon dioxide ≤ 40 mm Hg, followed by a stepwise lung-recruitment maneuver in pressure-controlled mode with increases of the peak inspiratory pressure (15 to 20 cm H2O) and positive end-expiratory pressure (3 to 10 cm H2O) for 30 min, and return to volume-controlled mode with a tidal volume of 15 ml/kg until reaching a peripheral oxygen saturation ≥ 96%. Weaning from the ventilator was achieved in six hours, and the patient was discharged two days after admission without neurological or respiratory deficits. Conclusions We present a rather unusual case of a neurogenic pulmonary edema subsequent to accidental electrocution in a dog. Timely diagnosis by ultrasound and mechanical ventilation settings are described. Our case highlights that pulmonary edema should be considered a potentially life-threatening complication of electrical shock in small animal emergency and critical care medicine.